INCLUSIVE EDUCATION PARADIGM IN ISLAM (Proceedings of International Conference on Special Education, 2019)
Awareness of inclusiveness in education that pays attention to the integration of regular students with students with special needs in the learning process, is often based on human values, narratives of fulfilling human rights, the principle of education for all and others who tend to be profane or worldly. So that religion tends to have no space in the discourse on inclusive education. The narrowness of the dialectical spaces regarding inclusive education could be because there are not many people who examine the relationship and contribution of religion to the concept of inclusive education. Even though there is no religion in its teachings to exclude the element of education from humans. Islam for example, has serious attention to education and human development. Islam also pays attention to equality of rights possessed by mankind especially in the aspect of education. Even the context of ' Education for all'has been carried out by Islam at the beginning of its development in the city of Makkah. The lack of a study of inclusive education in Islam, encourages some researchers to associate Islam with inclusive education. Unfortunately the study only portrays the intersection of Islamic teachings with the principle of inclusive education. Even though in the context of inclusive education itself, Islam does not only have contact but Islam is the spirit of inclusive education, that all human beings have the same educational rights. Through literature studies, this paper aims to portray the paradigm of Inclusion education in Islam so that it can be found that Islam is present as the spirit of the inclusive education.